Die Jesus van die geskiedenis: Hermeneutiese uitgangspunte in die ondersoek van J P Meier - Geyser, P. A. (HTS teologiese studies, 2001)
The Jesus of history: Hermeneutic premises in the research of JP Meier. The aim of this article is to reflect on the hermeneutical premises in the historical Jesus research of JP Meier. Of the intended three volumes two of Meier's books on Jesus have been published: A marginal Jew: Rethinking the historical Jesus, Volt: The roots of the problem and the person (1991); Vo12: Mentor, message, and miracles (1994). The article is structured along the following lines: first, Meier's points of departure are discussed according to certain hermeneutical criteria; second, Meier's views on the importance of historical Jesus research, the sources that he utilizes, and the criteria for historical discernment are discussed. A critical assesment of Meier's Jesus profile will be discussed in another article.